Full Dimensional Potential Energy Function and Calculation of State-Specific Properties of the CO+N2 Inelastic Processes Within an Open Molecular Science Cloud Perspective - Lombardi, Andrea; Pirani, Fernando; Bartolomei, Massimiliano; Coletti, Cecilia; Laganà, Antonio (Frontiers in Chemistry, 2019)
A full dimensional Potential Energy Surface (PES) of the CO + N2 system has been generated by extending an approach already reported in the literature and applied to N2-N2 (Cappelletti et al., 2008), CO2-CO2 (Bartolomei et al., 2012), and CO2-N2 (Lombardi et al., 2016b) systems. The generation procedure leverages at the same time experimental measurements and high-level ab initio electronic structure calculations. The procedure adopts an analytic formulation of the PES accounting for the dependence of the electrostatic and non-electrostatic components of the intermolecular interaction on the deformation of the monomers. In particular, the CO and N2 molecular multipole moments and electronic polarizabilities, the basic physical properties controlling the behavior at intermediate and long-range distances of the interaction components, were made to depend on relevant internal coordinates. The formulated PES exhibits substantial advantages when used for structural and dynamical calculations. This makes it also well suited for reuse in Open Molecular Science Cloud services.